Prognostics and health management: A review from the perspectives of design, development and decision - Hu, Yang; Miao, Xuewen; Si, Yong; Pan, Ershun; Zio, Enrico (Reliability engineering & system safety, 2022)
•The life cycle of prognostics and health management (PHM) is structuredinto DEsign, DEvelopment and DEcision phases (DE3).•Essences, key activities and interconnections of PHM DE3aresummarized.•Gaps, challengesand future researchdirectionsof PHM DE3are proposed. Prognostics and health management (PHM) is an enabling technology used to maintain the reliable, efficient, economic and safe operation of engineering equipment, systems and structures. In the last 5 years, many PHM review works have been published for discussing and summarizing the state-of-the-art of different approaches and methods, usage modes and applications of PHM. This paper intends to enrich the PHM state-of-the-art by reviewing the PHM works from three different points of view: DEsign, DEvelopment and DEcision (DE3). We dig into the problem essence of the DE3 of PHM by reviewing the research work, extracting the research conclusions from 235 related publications, and exposing the current methodologies and solution frameworks for addressing the DE3 issues. We identify the gaps and challenges of existing PHM concerning the DE3, and point out issues and opportunities of future PHM researches. We expect this review work to provide clear directions for assisting the researchers and practitioners in advancing the PHM methodologies and maturing them into practical PHM technologies.